2021
DOI: 10.1016/j.combustflame.2021.111598
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced reactivity of copper complex-based reactive materials via mechanical milling

Abstract: A prior investigation by the authors demonstrated that incorporating 25% of copper complex (Cu(NH3)4(NO3)2) into Al/CuO nanothermite enables to produce highly-reactive gasgenerating energetic composites for emerging micro-airbag applications. To further improve the decomposition of the copper complex into gaseous species (N2, O2, N2O), during the thermite reaction, we employed ball milling technique to diminish its grain size down to the nanoscale. Results show that premilling the copper complex i.e. refining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…The copper ammine complex (CuC), Cu(NH 3 ) 4 (NO 3 ) 2 , was synthesized and cryo-milled to reduce its size, as detailed in [17]. In brief, 4.83 g (0.02 mol) of copper nitrate trihydrate was dissolved in 10 mL of distilled water followed by the addition of 15 mL of 25% aqueous ammonia solution (0.24 mol).…”
Section: Energetic Composite Preparation and Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The copper ammine complex (CuC), Cu(NH 3 ) 4 (NO 3 ) 2 , was synthesized and cryo-milled to reduce its size, as detailed in [17]. In brief, 4.83 g (0.02 mol) of copper nitrate trihydrate was dissolved in 10 mL of distilled water followed by the addition of 15 mL of 25% aqueous ammonia solution (0.24 mol).…”
Section: Energetic Composite Preparation and Depositionmentioning
confidence: 99%
“…This so-called ultimate security device (USD) compatible with an embedded system environment can be actuated in less than 100 microseconds to mechanically disintegrate any types of components containing sensible data upon the detection of intrusion into the system. The actuation mechanism is provided by using a printed copper ammine complex-based energetic composite [16][17]; this material was chosen as it is a source of reliable, safe and "dormant" energy, exhibiting a long shelf life (decades) and able to very quickly deliver gas and heat through a self-sustained redox reaction. Whereas the Al/CuO thermite generates a very limited amount of gas, the addition of copper ammine complex greatly enhances the pressurization rate and gas generation so that to better achieve the component destruction.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, integrating nitrogen-rich explosives into nanothermites appears to be a promising approach for simultaneously obtaining high reaction heat and high gas generation. Recently, several works have been conducted on the combination of nanothermites with a variety of nitrogen-rich explosives, including RDX, CL-20, nitrocellulose, NaN 3 , , and TACN. , Although many of these works indicated that hybrid energetic composites exhibited better energetic performances than individual nanothermites and explosives, the nanothermite–explosive interaction and the influence of their ratios on performances still need systematic and in-depth investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several works have been conducted on the combination of nanothermites with a variety of nitrogen-rich explosives, including RDX, 21−24 CL-20, 24−26 nitrocellulose, 27−29 NaN 3 , 30,31 and TACN. 32,33 Although many of these works indicated that hybrid energetic composites exhibited better energetic performances than individual nanothermites and explosives, the nanothermite− explosive interaction and the influence of their ratios on performances still need systematic and in-depth investigations. Energetic coordination complexes (ECCs) are a class of intramolecular energetic materials based on energetic ligands and anions in coordination structures.…”
Section: Introductionmentioning
confidence: 99%
“…Secondarily, as prestressing has been shown to improve the reactivity of Al, the rapid energy released during TACN decomposition can be potentially employed to shock-heat and induce strain in the Al nanoparticles. Hence, this approach may be able to mitigate the preprocessing steps associated with the annealing. Previous explorations have shown that the use of supermicrometer TACN particles as gas generating additives can significantly improve the reactivity of Al/CuO composites. However, the application of nanoscale TACN for in-situ stress induction in Al nanoparticles has not been explored.…”
Section: Introductionmentioning
confidence: 99%